2015
DOI: 10.1016/j.jalz.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

C‐terminal neurogranin is increased in cerebrospinal fluid but unchanged in plasma in Alzheimer's disease

Abstract: This study strengthens the potential of neurogranin as an AD CSF biomarker, which now needs validation in larger studies. As tools, straightforward immunoassays can be used, as demonstrated by the described ELISA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
112
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 42 publications
9
112
1
Order By: Relevance
“…They are linked to the disruption of amyloid metabolism and plaque pathology, and to the cortical neurodegeneration occurring in the disease [39]. Since levels of neurogranin are increased in the CSF of AD patients, while they are decreased in AD brains, this protein has also been discussed as a potential AD biomarker [17, 18, 19, 20, 21, 22]. Moreover, studies have suggested that neurogranin might be an AD-specific biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are linked to the disruption of amyloid metabolism and plaque pathology, and to the cortical neurodegeneration occurring in the disease [39]. Since levels of neurogranin are increased in the CSF of AD patients, while they are decreased in AD brains, this protein has also been discussed as a potential AD biomarker [17, 18, 19, 20, 21, 22]. Moreover, studies have suggested that neurogranin might be an AD-specific biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…This can indirectly be observed by measuring levels of the postsynaptic protein neurogranin in brain tissue [10, 11, 12]. Decreased levels of neurogranin, a protein that has a key role in long-term potentiation and learning [13, 14, 15], have been found in brains of AD patients [10, 16], while CSF neurogranin levels are increased [17, 18, 19, 20]. Studies have suggested that increased CSF neurogranin levels might even be predictive of progression from MCI to AD; thus, this protein has also been discussed as a potential AD biomarker [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…CSF neurogranin levels are higher in AD [63, 175, 190, 221, 242, 291, 310, 347, 354, 361] or MCI patients [291, 347] compared with controls or non-AD dementia patients [354]. Higher levels of CSF neurogranin have been reported in AD compared with MCI [138, 291], although there was no significant difference between AD and MCI Aβ-positive (based on CSF Aβ42) groups in a recent study of the ADNI cohort [347].…”
Section: Synaptic Dysfunctionmentioning
confidence: 99%
“…To date, no significant differences have been reported in plasma levels of neurogranin between patients with AD and controls [63, 190]. However, levels of neurogranin in neuronally derived exosomes in plasma have been found to be lower in AD patients compared with controls [110, 389], as well as in MCI subjects who progressed to AD compared with stable MCI subjects [389].…”
Section: Synaptic Dysfunctionmentioning
confidence: 99%
“…Synaptic loss has been reported to occur very early in the natural history of AD, therefore neurogranin can be a valuable biomarker of early, possible preclinical, stage of the disease [23]. Neurogranin concentrations are significantly increased in mild cognitive impairment (MCI) [24, 25] and can be a predictive factor of conversion to dementia.…”
Section: Introductionmentioning
confidence: 99%